A Flexible Yet Robust 3D-Hybrid Gel Solid-State Electrolyte Based on Metal–Organic Frameworks for Rechargeable Lithium Metal Batteries - Ruliang Liu; Jiaqi Xue; Lijun Xie; Huirong Chen; Zhaoxia Deng; Wei Yin (Gels)
Compared to traditional liquid electrolytes, solid electrolytes have received widespread attention due to their higher safety. In this work, a vinyl functionalized metal–organic framework porous material (MIL-101(Cr)-NH-Met, noted as MCN-M) is synthesized by postsynthetic modification. A novel three-dimensional hybrid gel composite solid electrolyte (GCSE-P/MCN-M) is successfully prepared via in situ gel reaction of a mixture containing multifunctional hybrid crosslinker (MCN-M), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), ethylene carbonate (EC), diethylene glycol monomethyl ether methacrylate (EGM) and polyethylene (vinylidene fluoridee) (PVDF). Benefiting from the excellent mechanical properties, rich pore structure, and numerous unsaturated metal sites of GCSE-P/MCN-M, our GCSE-P/MCN-M exhibits excellent mechanical modulus (953 MPa), good ionic conductivity (9.3 × 10−4 S cm−1) and wide electrochemical window (4.8 V). In addition, Li/LiFePO4 batteries based on GCSE-P/MCN-M have also demonstrated excellent cycling performance (a high-capacity retention of 87% after 200 cycles at 0.5 C). This work provides a promising approach for developing gel solid-state electrolytes with high ion conduction and excellent safety performance.